The Particle Radiobiology of Multipotent Mesenchymal Stromal Cells: A Key to Mitigating Radiation-Induced Tissue Toxicities in Cancer Treatment and Beyond? - Rühle, Alexander; Grosu, Anca-Ligia; Nicolay, Nils H. (Frontiers in Oncology, 2021)
Mesenchymal stromal cells (MSCs) comprise a heterogeneous population of multipotent stromal cells that have gained attention for the treatment of irradiation-induced normal tissue toxicities due to their regenerative abilities. As the vast majority of studies focused on the effects of MSCs for photon irradiation-induced toxicities, little is known about the regenerative abilities of MSCs for particle irradiation-induced tissue damageor the effects of particle irradiation on the stem cell characteristics of MSCs themselves. MSC-based therapies may help treat particle irradiation-related tissue lesions in the context of cancer radiotherapy. As the number of clinical proton therapy centers is increasing, there is a need to decidedly investigate MSC-based treatments for particle irradiation-induced sequelae. Furthermore, therapies with MSCs or MSC-derived exosomes may also become a useful tool for manned space exploration or after radiation accidents and nuclear terrorism. However, such treatments require an in-depth knowledge about the effects of particle radiation on MSCs and the effects of MSCs on particle radiation-injured tissues. Here, the existing body of evidence regarding the particle radiobiology of MSCs as well as regarding MSC-based treatments for some typical particle irradiation-induced toxicities is presented and critically discussed.